SAT0637-HPR Impairment in the Activities of Daily Living in Older Adults with and Without Osteoporosis, Osteoarthritis and Chronic Back Pain: Results of a Population-Based Cross-Sectional Study. (9th June 2015) - Stamm, T.A.; Pieber, K.; Smolen, J.; Dorner, T.
Abstract : Background: Independence in performing activities of daily living (ADLs) is a central aspect of functioning. Older adults frequently experience impairments and limitations in functioning in various life areas. Objectives: The aim of this survey was to explore the limitations in the activities of daily living in older adults in a population-based survey in Austria. Methods: 3097 subjects aged ≥65 years of the Austrian health interview survey formed the cohort of this analysis. Descriptive statistics were used to calculate frequencies of problems in the ADLs. A principal component analysis was applied to analyze the main dimensions of 19 items of ADL. Binary logistic regression models were used with the ADL dimensions as the dependent variables and osteoarthritis, chronic back pain, osteoporosis, sex, education level, anxiety or depression, age and pain intensity as independent variables. Results: People with musculoskeletal conditions were significantly more often affected by ADL problems than people without these diseases. The ADL domain which caused problems in the highest proportion of people was "doing heavy housework" (43.9%), followed by "bending or kneeling down" (39.3%), "climbing stairs up and down without walking aids" (23.1%), and "walking 500 meter without walking aids" (22.8%). The principal components analysis revealed four dimensions of ADLs: (1) intense "heavy burden" ADLs, (2) basic instrumental ADLs, (3) basic ADLs and (3) hand-focused ADLs. The proportion of subjects who had problems with the respective dimensions was 58.2%, 29.2%, 23.0%, and 9.2%. Anxiety/ depression (greatest effect), followed by the chronic musculoskeletal disease itself, female sex, higher age and pain intensity were significant predictors of ADL problems. Conclusions: This population-based survey indicates that older people have considerable ADL problems. Older adults with musculoskeletal complaints could be a special target group for ADL specialists such as physical medicine and rehabilitation physicians and occupational therapists. More attention should be paid to the high impact of pain intensity, anxiety and depression on ADLs. Disclosure of Interest: None declared